CALCULATION OF THE STRUCTURAL AND NMR PROPERTIES OF THE TRIDECAMERIC ALO4AL12(OH)24(H2O)127+ POLYCATION - Tossell J.A. (My University, 2001)
The aluminum tridecameric polyoxocation, AlO4Al12(OH)24(H2O)127+ is a major component in partially hydrolyzed Al+3(aq) solutions and has been extensively studied experimentally, mainly using NMR techniques. I have calculated the equilbrium geometry of this cation using the Hartree-Fock method and a polarized double-zeta effective core potential basis set, obtaining bond distances which agree well with X-ray crystallographic studies of selenate and sulfate salts of the polycation (Al[4]: 4 x 1.85 Α calc, 4 x 1.84 Α exp: Al[6]: 4 x 1.85, 2 x 2.05 Α calc, 2 x 1.84, 2 x 1.88, 1.91, 2.04 Α exp [where the numbers in brackets indicate the coordination numbers]). I have also calculated electric field gradients and NMR shielding constants at all the atoms using the standard 6-31G* basis set and Hartree-Fock and hybrid Hartree-Fock-density functional (B3LYP) techniques. Using the Hartree-Fock method, the central four-coordinate Al is calculated to be deshielded by ~56 ppm, and the six-coordinate Al atoms by ~16 ppm, vs. the Al(OH2)6+3 reference, compared to experimental shifts of 63 and 12 ppm, respectively. The central Al[4] is thus shielded by ~20 ppm with respect to the tetrahedral monomer Al(OH)4-1. Al-NMR shifts obtained from the B3LYP calculations are very similar. The calculated O-NMR shifts, vs. free gas-phase H2O, are 17 ppm for the η-OH2 groups, 30 ppm for the μ-OH and μOH' groups, and 55 ppm for the μ4-O group, which match well with the experimentally assigned shifts of 20, 30, and 55 ppm, respectively (vs. liquid H2O). The B3LYP method yields O shifts, which are systematically about 40 to 50% larger. It is not clear whether the discrepancies in the calculated O shifts vs. liquid water are a result of deficiencies in the model (neglect of the aqueous environment) or in the method (lack of correlation in the Hartree-Fock method). Studies on the Al2(OH)2(OH2)8+4 cation with small numbers of explicit waters hydrogen-bonded to it indicate that O shifts can be perturbed strongly by the presence of solvent. The calculated 17O nuclear quadrupole coupling constants, NQCC (using the 6-31G* Hartree-Fock calibration factor of Ludwig et al., 1996 to relate electric field gradients to NQCC values) are 1.7 MHz for μ4-O, 7.8 to 8.0 MHz for the μOH and μOH' groups and 10.7 MHz for the ηOH2 group. The μOH values are substantially higher than experimental values of 5 to 6 MHz observed for Al2OH groups in Al oxyhydroxides. B3LYP values are very similar. However, hydrogen bonding to water in simple model compounds like Al2(OH)2(OH2)8+4 reduces the -OH NQCC values to ~6 MHz.